2013
DOI: 10.1371/journal.pone.0057834
|View full text |Cite
|
Sign up to set email alerts
|

Role of Endogenous Cortistatin in the Regulation of Ghrelin System Expression at Pancreatic Level under Normal and Obese Conditions

Abstract: Ghrelin-system components [native ghrelin, In1-ghrelin, Ghrelin-O-acyltransferase enzyme (GOAT) and receptors (GHS-Rs)] are expressed in a wide variety of tissues, including the pancreas, where they exert different biological actions including regulation of neuroendocrine secretions, food intake and pancreatic function. The expression of ghrelin system is regulated by metabolic conditions (fasting/obesity) and is associated with the progression of obesity and insulin resistance. Cortistatin (CORT), a neuropept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…Based on previous results showing that In1-ghrelin variant can promote features of aggressiveness in breast cancer [ 13 ] and pituitary tumor cells [ 16 ], and on the results of our study, which demonstrated that the expression of the In1-ghrelin variant is a valuable marker to classify patients according to prognosis, we further explored the functional role of In1-ghrelin in two NET cell models. In vitro data revealed that overexpression of In1-ghrelin enhanced features of aggressiveness in human NET cells (i.e.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Based on previous results showing that In1-ghrelin variant can promote features of aggressiveness in breast cancer [ 13 ] and pituitary tumor cells [ 16 ], and on the results of our study, which demonstrated that the expression of the In1-ghrelin variant is a valuable marker to classify patients according to prognosis, we further explored the functional role of In1-ghrelin in two NET cell models. In vitro data revealed that overexpression of In1-ghrelin enhanced features of aggressiveness in human NET cells (i.e.…”
Section: Discussionmentioning
confidence: 86%
“…Soon after the discovery of native ghrelin, a number of alternative ghrelin gene-derived peptides and mRNA splice variants were identified [ 9 , 14 ]. One of these splice forms, the In1-ghrelin variant, is also expressed in the GIT and pancreas [ 15 , 16 ]. In1-ghrelin peptide shares the initial 13 aa with native ghrelin, including the first 5-aa, which is the minimum sequence required for ghrelin acylation by GOAT and for binding and activation of GHSR1a [ 9 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, obestatin probably plays a relevant role in the promotion of human islet cell survival and b-cell functioning (Granata et al 2008). Recent observations have also suggested that other ghrelin gene-derived molecules could be present in the endocrine pancreas, as in the case of the In1-ghrelin variant (Chanclon et al 2013), where it might play a functional role, which merits further investigation.…”
Section: Posterior Pituitary Hormonesmentioning
confidence: 99%
“…In addition to their roles in the CNS, both peptides also regulate endocrine secretion. CORT has been shown to bind with high affinity to the ghrelin receptor (GHSR) and play important actions on pancreatic function (41). In islets isolated from C57BL6 mice, CORT action has been reported to reduce the glucose-stimulated insulin secretion (42).…”
Section: Discussionmentioning
confidence: 99%